2022
DOI: 10.1097/sap.0000000000003085
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Rectourethral Fistula Recurrence With Gracilis Flap

Abstract: Background Rectourethral fistula (RUF) is an uncommon serious condition with various etiologies including neoplasm, radiation therapy, and surgery. Treatment for RUF remains problematic with a high recurrence rate. Although studies have suggested the recurrence rate of RUF is lower after surgical repair using a gracilis flap, outcomes have varied and the studies were small and inadequately controlled. Here, we compare outcomes of RUF repair with and without gracilis flap to evaluate its efficacy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…This creates better surgical conditions, makes the journey less traumatic for affected patients, and can potentially reduce the tendency for recurrence. In 2022, Park et al published a study in which surgical closure of rectourethral fistulas had been performed and observed that significantly fewer recurrences occurred in patients ( n = 24) treated with gracilis interposition compared to a control group [ 36 ]. The current authors’ approach is in line with the statement of Corte et al [ 4 ], who analyzed different treatment management strategies in 79 patients with rectovaginal fistulas.…”
Section: Discussionmentioning
confidence: 99%
“…This creates better surgical conditions, makes the journey less traumatic for affected patients, and can potentially reduce the tendency for recurrence. In 2022, Park et al published a study in which surgical closure of rectourethral fistulas had been performed and observed that significantly fewer recurrences occurred in patients ( n = 24) treated with gracilis interposition compared to a control group [ 36 ]. The current authors’ approach is in line with the statement of Corte et al [ 4 ], who analyzed different treatment management strategies in 79 patients with rectovaginal fistulas.…”
Section: Discussionmentioning
confidence: 99%